FROM PLAYLIST TO PRONUNCIATION: EXPLORING STUDENTS’ VIEWS ON SPOTIFY IN LANGUAGE LEARNING - Daniyati, Sukma; Suwaebatul Aslamiya; Handrianto Saputra (Juliet, 2025)
This study explores students’ perceptions of using the Spotify application as a tool to improve English pronunciation. Conducted at SMA Negeri 4 Tanjungpinang, the research involved 32 students who responded to a structured questionnaire. The aim was to understand how students engage with English songs on Spotify and how they perceive its effectiveness in supporting pronunciation learning. The results show that the majority of students held positive perceptions, viewing Spotify as a helpful resource for pronunciation improvement through repeated listening and exposure to native speaker models. A significant 78.13% of students reported using Spotify specifically to enhance pronunciation, with many focusing on suprasegmental features such as intonation (75%), stress (80.65%), and rhythm (77.42%). These elements are essential for achieving natural-sounding and intelligible English speech. However, only 41.94% of students reported noticeable improvement, indicating that passive listening may not be sufficient for pronunciation development. This suggests that while Spotify provides accessible and authentic input, it must be supported by structured strategies such as repetition, shadowing, and phonetic awareness activities. Furthermore, 59.38% of students expressed willingness to recommend using Spotify for pronunciation, showing moderate endorsement. Pop songs were identified as the most helpful genre due to their clear lyrics, repetitive patterns, and moderate tempo. These findings underscore the potential of music-based learning as a motivational and effective supplement to formal pronunciation instruction. To maximize results, educators are encouraged to integrate music platforms like Spotify into classroom activities that promote active listening and pronunciation practice.